The Implementation of Cooperative Learning Model ‘Number Heads Together (NHT)’ in Improving the Students’ Ability in Reading Comprehension - Mayong Maman; Andi Aryani Rajab (Institute of Advanced Engineering and Science, 2016)
The study aimed at describing the implementation of cooperative learning model of (NHT) at student of SMPN 2 Maros. The method used was a classroom action research in two cycles. Data were collected using the test for the quantitative and non-test for the qualitative by employing observation, field note, student’s workbook, student’s reflection sheet, and test of learning outcomes. The improvement of competence on cycle I was 44% that was categorized as extremely good, 56% were categorized as good, and no student was categorized as low. Cycle II, 84% were classified as extremely good, 16% were grouped as good, and no one was classified as low.